PHYTOCHEMICAL ANALYSIS, ANTIMICROBIAL AND ANTIOXIDANT ACTIVITY OF ETHANOLIC EXTRACT OF VERNONIA ANTHELMINTICA - CH.SANTOSH; IDRESS HAMAD ATTITALLA; M.MADAN MOHAN (International Journal of Pharma and Bio Sciences, 2013)
Vernonia anthelmintica is a wild medicinal herb distributed throughout the India. It is used as a folk medicine against cough, skin diseases, diarrhea and fever. In the present study, ethanolic extract was obtained from seeds of Vernonia anthelmintica and phytochemical analysis was done to screen alkaloids, saponins, steroids, carbohydrates, flavonoids, glycosides, polyphenols and gums and mucilage. Antimicrobial activity was carried out by using four bacterial strains Staphylococus aureus, E. coli, Pseudomonas aeruginosa, Bacillus subtilis and two fungal strains such as Aspergillus niger and Trichophyton rubrum. This ethanolic extract showed good antibacterial activity against Bacillus subtilis (20.21±0.8mm) and Pseudomonas aeruginosa (19.25±0.6) whereas moderate activity against Staphylococcus aureus (15.34±0.5) and E. coli (14.56±0.8). Whereas ethanolic extract showed good anti-fungal activity against Aspergillus flavus (19.64±1.8) and showed moderate activity against Trycophyton rubrum (13.21±1.1) at highest concentration of ethanolic extract 80mg/ml concentration. V.antihelmintica seed ethanolic extract showed good free radical scavenging activity at all concentrations of ethanolic extract. Our results clearly saying that seed ethanolic extract showed high content of phytochemicals, highest antimicrobial and antioxidant activity and our results supported the usage of Vernonia anthelmintica in folk and traditional medicine.